An Overview on Betel Quid and Areca Nut Practice and Control in Selected Asian and South East Asian Countries. (1st June 2020) - Gunjal, Shilpa; Pateel, Deepak Gowda Sadashivappa; Yang, Yi-Hsin; Doss, Jennifer Geraldine; Bilal, Sobia; Maling, Thaddius Herman; Mehrotra, Ravi; Cheong, Sok Ching; Zain, Rosnah Binti Mohd
Abstract: Background: Areca nut (AN) and betel quid (BQ) chewing are ancient practices followed by an extensive proportion of the world's population. These practices are endemic in larger parts of South and Southeast Asia and selected Western Pacific countries. The prevalence of these habits varies across regions, age, gender, cultural practice, and socioeconomic status groups. Considerable variations exist between countries with respect to prevention/intervention programs, and policy guidelines of BQ usage. Objectives: (1) To provide an overview of the BQ chewing prevalence, practices, preventive interventions and policies in selected Asian and Western Pacific countries. (2) To explore the different terminologies associated with BQ use. Method: A narrative review of the current literature related to BQ, AN, and oral cancer was conducted by searching PUBMED, CINAHL, and GOOGLE databases. Results: The literature review revealed that the prevalence of BQ was found to be highest in Papua New Guinea, followed by Bangladesh, India, Pakistan, Myanmar and Sri Lanka. While, Cambodia, Malaysia, Indonesia and Taiwan had comparatively lower prevalence. Smokeless tobacco, BQ with tobacco, BQ without tobacco, AN were some of the terminologies used for BQ in various studies. Conclusions: The prevalence, and the interventional policies related to BQ and AN chewing habits varies widely among the selected countries. With the increasing awareness and association of BQ with oral cancer, there is a need to have better awareness, prevention and interventional strategies in place. We also found considerable variation in the use of terminologies associated with BQ.